If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3cox(x) + 2sin(x) = 0 Multiply cox * x 3cox2 + 2sin(x) = 0 Multiply ins * x 3cox2 + 2insx = 0 Solving 3cox2 + 2insx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2insx' to each side of the equation. 3cox2 + 2insx + -2insx = 0 + -2insx Combine like terms: 2insx + -2insx = 0 3cox2 + 0 = 0 + -2insx 3cox2 = 0 + -2insx Remove the zero: 3cox2 = -2insx Divide each side by '3ox2'. c = -0.6666666667ino-1sx-1 Simplifying c = -0.6666666667ino-1sx-1
| 23x=5x^2 | | 4x-(3y-z+2)= | | 4x-4=16# | | log(-x)=-log(x) | | 7e+5e= | | 74=a^3+b^3+c^3 | | Y+X=30 | | 6z+5=9+3z | | 8x+6=64 | | 3(2a-4)-4(2a-6)=72 | | 2a-(8a+3a)= | | 4x-2cosx=0 | | 15x-9=-19 | | 3cosx+2sinx+2=0 | | 4b+7=11+b | | 5=4+2n | | 16-17m=30 | | 12+x=-22 | | 2x=2y+10 | | 17=8+2Q | | t/-1=16 | | 17+8+2Q=17+20-Q | | 16+x=26 | | 3-14x+9=5x+2 | | 5-2k=18 | | 4u-3=-20 | | a(a-2b)+b(2b-a)=0 | | -3(-4x+5)=-12x-5 | | 6(7x+5)=-8x | | 8+4(-7x-3)=10 | | -5=-(n-3) | | -(x+8)+2=-3 |